ภาพรวมของปรากฏการณ์ “สาวพริตตี้” ในงานมอเตอร์โชว์ An Overview of “Pretty Girl” Phenomenon at Motor Show - วงษ์สาธิตศาสตร์ ฐาปะนะ (วารสารรามคำแหง ฉบับมนุษยศาสตร์, 2014)
บทคัดย่อ ‘สาวพริตตี้’ หรือที่เรียกสั้น ๆ ว่า ‘พริตตี้’ ถูกนำมาใช้เป็นเครื่องมือในการสื่อสารการตลาดที่ได้รับความนิยมเป็นอย่างสูงโดยเฉพาะอย่างยิ่งในงานมอเตอร์โชว์ นักการตลาดใช้ พริตตี้ในการสร้างสีสัน และความดึงดูดใจให้เกิดขึ้นกับกลุ่มเป้าหมายซึ่งนับเป็นการใช้กลยุทธ์ด้าน ‘เพศสรีระ’ ในการตลาดเชิงกิจกรรมที่มีประสิทธิผล อย่างไรก็ตาม จากการศึกษา พบว่า ‘พริตตี้’ ไม่มีผลต่อพฤติกรรมการตัดสินใจซื้อของผู้บริโภคในกลุ่มสินค้าที่มีการทุ่มเท ความพยายามในการซื้อสูง อาทิเช่น รถยนต์ เป็นต้น และเมื่อวิเคราะห์ปรากฏการณ์พริตตี้ใน งานมอเตอร์โชว์ผ่าน ‘ทฤษฎีสตรีนิยม’ พบว่า อาชีพดังกล่าวเกิดจากแนวคิดระบบปิตาธิปไตย (สังคมที่ผู้ชายเป็นใหญ่) ด้วยการสร้างให้ผู้หญิงเป็นวัตถุทางเพศที่มีไว้เพื่อตอบสนองการจ้องมองแบบเพศชาย ความหมายของพริตตี้ถูกสร้างขึ้น ตอกย้ำ และกระทำซ้ำผ่านการสื่อสารการตลาดและสื่อสารมวลชนมาโดยตลอด โดยเฉพาะสื่อมวลชนนับว่ามีอำนาจอย่างมากในการสร้างความหมายของพริตตี้โดยผ่านการคัดเลือกความหมาย การกำหนดวาระ และการนำเสนอ ต่อประชาชนในแง่มุมต่าง ๆ ส่งผลต่อทั้งภาพลักษณ์ของ ‘อาชีพ พริตตี้’ และตัวของ ‘พริตตี้’ เอง วาทกรรมและมายาคติทางเพศต่าง ๆ ได้ถูกสร้างขึ้นทั้งด้านบวกและด้านลบ นำไปสู่ความขัดแย้งทางด้านความคิดที่เกิดขึ้นในสังคม นอกจากนี้ ปรากฏการณ์สาวพริตตี้ในงานมอเตอร์โชว์ ยังนับเป็นการสะท้อนให้เห็นถึงปัญหาด้านการสื่อสารทางเพศที่ละเอียดอ่อนในสังคมไทย อีกด้วย สำหรับข้อเสนอแนะในการแก้ไขปัญหาดังกล่าว ทุก ๆ ภาคส่วนจำเป็นต้องเรียนรู้และทำ ความเข้าใจเกี่ยวกับเพศสภาพและเพศวิถีของคนในสังคม เปิดใจกว้างยอมรับ ร่วมกันทบทวนตรวจสอบวาทกรรมและมายาคติทางเพศต่าง ๆ ที่นำเสนอผ่านสื่อมวลชนที่ก่อให้เกิดความขัดแย้งในสังคม ร่วมกันวิพากษ์วิจารณ์ สะท้อนความคิดเห็น รวมถึงร่วมกันรื้อถอนมายาคติทางเพศที่ขัดต่อวัฒนธรรมและประเพณีอันดีงามของไทย และสรรสร้างมายาคติทางเพศที่สอดคล้องกับบริบทของสังคมในปัจจุบันขึ้นทดแทน อันจะเป็นวิถีทางที่นำไปสู่การสื่อสารทางเพศที่มีประสิทธิภาพในอนาคต Abstract ‘Pretty Girl’ or ‘Pretty’, an attractive woman with good personality who represents products and brands, is widely used as an effective tool in marketing communication, especially at the Motor Show –an international automobile business trade fair. According to marketing perspective, ‘Pretty’ does not influence consumers’ purchasing behavior in high involvement product like automobile. Marketers only use ‘Pretty’ to invigorate and attract targeted customers’ attention, which is known as the efficient ‘sex strategy’ in event marketing activity. Based on the feminist theory, the analysis of ‘Pretty Girl’ phenomenon at the Motor Show indicates that ‘Pretty’, as an occupation, was emerged under the concept of ‘patriarchy’; a form of social organization in which a male is the family head and the title is traced through the male line, by making female as ‘sex object’ in order to serve ‘male gaze’ concept in our society. Then and since, the meaning of ‘Pretty’ has been constructed, repeated and reproduced through marketing communication, and especially in mass media. This phenomenon also shows the roles of the mass media as the major encoder in meaning construction of ‘Pretty’, over the meaning selection and agenda setting, and disseminates messages to audiences. Thus, certain perceived meanings and images of ‘Pretty Girl’ and ‘Pretty’ as an occupation are emerged among audiences. Consequently, sexual discourses and myth, in either positive or negative side, are also created, causing the conflict of thoughts in a row. Indeed, the ‘Pretty Girl’ phenomenon at Motor Show has also reflected the sensitive gender communication problem in Thai society. For the resolving recommendation, this article hints that the importance of better understanding of ‘gender’ and ‘sexuality’ must be raised among every concerning organization in the society. In addition, the disputable sexual discourses and myths that are represented within the mass media and the society should be reexamined. Moreover, critical evaluation of sexual discourses and myths, which are contrary to virtues of Thai culture and customs, must be considered, whilst the meaning reconstruction of the sexual myths conforming to the current social context should be replaced. Those are the ways to reach an effective gender communication in the future.